Η ΣΥΝΤΕΧΝΙΑ ΤΩΝ ΥΠΟΔΗΜΑΤΟΠΟΙΩΝ ΣΤΗ ΒΕΝΕΤΟΚΡΑΤΟΥΜΕΝΗ ΚΕΡΚΥΡΑ - ΚΑΡΛΑΦΤΗ-ΜΟΥΡΑΤΙΔΗ, ΦΩΤΕΙΝΗ (Eoa kai Esperia, 2007)
This study refers to one of the most important crafts of the seventeenthcentury: the craft (Arte) of the shoemakers. Specifically, it attempts toinvestigate and review the factors affecting the process of conducting electionsfor the appointment of the trade union dignitaries, these being: place, time, right to vote and be voted for, problems resulting from the insubordination tolaws and also the adjournment or delay of these elections. Furthermore, the paper examines the areas of competence of the tradeunion and other dignitaries. It discusses their duties, which include themanagement of the craft's internal affairs so as to ensure its proper and harmonious functioning. In addition to these duties, the union dignitaries alsorepresented their fellow craftsmen in the Regimento, thus assuming a politicalrole, and recommended the principal officials of the craft's auditing procedure. In conclusion and supplementary to the above, the rights and obligationsof the simple members of the trade union are mentioned, along with themanner in which the profession was conducted.